Spatiotemporal assessment of benthic macroinvertebrate communities in the Bermejo River Basin in the Ecuadorian Amazonia - Federico Sinche Chele; Manuel Cabrera Quezada; Roly Ramirez; Augusto Vargas; Jessica Cayambe; Jennifer Alvarez; Pablo Carrera; Hayda Andrade; Edison Segura (Limnology and Oceanography Letters)
Abstract The Cofán communities rely on the Cofán Bermejo Ecological Reserve for their survival and cultural practices. Due to the rugged and inaccessible topography of the reserve in the Northern Ecuadorian Amazon region, limited biomonitoring and ecological characterization studies of the ecosystem health have been conducted. We investigated the community composition and functional structure of benthic macroinvertebrates in the Bermejo River basin by identifying bioindicators and measuring physicochemical variables. Our results indicated that predators were consistently the dominant taxa in all sampled sites, and that the taxonomic abundance was positively correlated with richness and the collector taxa. We also observed positive relations between pH and taxonomic abundance, and between water temperature and the biological monitoring working party metric. Primary associations were also found between feeding guilds, pollution‐sensitive taxa, and ecological water indices. This work provided a first characterization of the macroinvertebrate communities and physicochemical parameters in the Bermejo River basin.